Validity and reliability of the Arabic community integration questionnaire in a Lebanese sample of adults with physical disability - Nour El Hoda Saleh; Ali Orabi; Sleiman Fneish; Bilal Cheaito; Ibrahim Naim (PLoS ONE, 2025)
Background Community integration is a critical factor influencing the quality of life for individuals with physical disabilities. However, there is a lack of culturally adapted tools to assess community integration in Arabic-speaking populations. This study aimed to translate, validate, and examine the psychometric properties of the Arabic version of the Community Integration Questionnaire (AR-CIQ) among Lebanese adults with physical disabilities. Methods A total of 150 individuals with various physical disabilities participated in the study. The AR-CIQ was translated and adapted to the Lebanese cultural context. Exploratory Factor Analysis (EFA) was conducted to determine the factor structure, while reliability was assessed using Cronbach’s alpha coefficients. Correlations between community integration and quality of life (QOL) were also explored using the SF-12 questionnaire. Results The EFA revealed a four-factor structure of the AR-CIQ, which explained 68.27% of the total variance. These factors included social outdoor integration, productive and social management, domestic integration, and social support. The reliability of the AR-CIQ subscales varied, with the domestic integration subscale showing excellent internal consistency (α = 0.830). Correlation analysis revealed significant associations between community integration and QOL, with the mental health component (MCS-12) showing a moderate positive correlation with community integration (r = 0.418, p < 0.01). Conclusion The AR-CIQ is a valid and reliable tool for assessing community integration in Lebanese adults with physical disabilities. Its factor structure reflects the unique cultural and contextual aspects of Lebanon. This study highlights the need for culturally sensitive tools in disability research and suggests that enhancing community integration could improve mental health outcomes for individuals with physical disabilities. Future research should explore longitudinal outcomes and the effectiveness of community-based interventions to further support the integration of individuals with disabilities in Lebanese society.